Why did agricultural labour productivity not converge in Europe from 1950 to 2005? - Miguel Martín-Retorillo; Vicente Pinilla (European Historical Economics Society (EHES), 2012)
This paper offers a long-term analysis of agricultural labour productivity differences in Europe using econometric techniques. The results show the crucial importance of the land/labour ratio. The continuous exit of manpower from the sector, coupled with increased use of productive factors originating in other sectors of the economy, caused the efficiency of agricultural workers to rise. The different relative importance of these processes across countries largely explains why labour productivity did not converge. In turn, institutions have apparently conditioned differences in productivity, as a direct and inverse relation is detected between membership of the EU and the Communist block and the productivity of agricultural labour.
Keywords: N50; N54; O13; Q10; 330; Agricultural labour productivity; European agriculture 20th century; European economic development